2013
DOI: 10.1080/13588265.2013.853965
|View full text |Cite
|
Sign up to set email alerts
|

The effect of mass properties on road accident reconstruction

Abstract: The paper investigates the influence of vehicle mass properties (mass, centre of gravity location, inertia tensor) on accident reconstruction. Considering the case of two colliding vehicles, the paper aims at defining which is the uncertainty of each mass property that should be prescribed to obtain an accurate accident reconstruction. The paper is divided into two parts. The first part presents a mathematical model, and its validation, able to perform a proper computation of the motion of vehicles before and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…The result of speed alone is not enough to explain the pedal force effect on the braking distance, particularly for those involving heavy vehicles. GVW is also an important factor that needs to be considered in braking distance calculations with varying pedal force [8]. Figure 2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The result of speed alone is not enough to explain the pedal force effect on the braking distance, particularly for those involving heavy vehicles. GVW is also an important factor that needs to be considered in braking distance calculations with varying pedal force [8]. Figure 2.…”
Section: Resultsmentioning
confidence: 99%
“…This is owing to the complicated braking systems used in heavy vehicles, with different possible failure modes and performance characteristics, including locked-wheel braking and longer braking distances than those for passenger cars [7]. Moreover, as stated by Gobbi (2014), the vehicle GVW varies considerably with different loading conditions and also shows a strong association with loss of control and the inability to stop the vehicle safely [8]. However, speed and GVW are not the only factors that lead to road accidents [9][10][11]; past studies indicate that the rate of road accidents increases during rainy weather because it reduces the road surface's coefficient of friction [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…The new test rigs (InTenso+ and InTensino+) are able to identify both the inertia tensor and the centre of gravity location during one single experiment. An application of this approach for road accident reconstruction is given in [1]- [3]. This problem is also considered in [33].…”
Section: Introductionmentioning
confidence: 98%
“…The inertia parameters have a strong effect on dynamics of rigid mechanical systems and must be known precisely for the precise control of its motion. Inertia parameters identification is very important for road accident reconstruction [1]- [4], and for spacecrafts and aircrafts [5]- [8] .A common practice for the estimation of rigid body inertia parameters is computation of them using CAD software. However computer estimation methods are not reliable due to possible errors and uncertainties in geometry, in density of the material and of the real rigid bodies and mechanical systems.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have shown that the heavy vehicles' characteristic, loading condition, and speed play significant roles in road safety (Fancher & Campbell, 1995;Gobbi, Mastinu, & Previati, 2014;Seipel, Baumann, Hermanutz, & Winner, 2013). Additionally, the tire and pavement friction are also serious contributing factors that lessen the potential for crashes.…”
Section: Introductionmentioning
confidence: 99%